PEMBERDAYAAN MASYARAKAT MELALUI USAHA PEMBENIHAN IKAN LELE DI DESA TELADAN KABUPATEN REJANG LEBONG - Rahmadiah, Triayu; Hamka, Muhammad Subhan; Nafsiyah, Ikromatun; Prawanto, Andika; Sari, Kiky Nurfitri; Nur’aini, Nur’aini (Universitas Mataram, 2024)
The economic structure of Bengkulu Province is still dominated by agriculture, forestry and fisheries businesses, one of which is in Teladan Village, Rejang Lebong Regency. One of the productive businesses that can be developed is catfish hatchery. However, this activity has not been running optimally due to several obstacles and barriers such as the lack of public understanding of catfish cultivation, especially the availability of quality and sustainable seeds. This activity aims to make a positive contribution to the community through empowering productive businesses that are in accordance with the needs and potential of the community, so as to improve the welfare and independence of the community. The method used in community service activities is to use participatory methods, namely methods that involve the community as partners and subjects of activities through socialization and training activities. Based on the results of distributing pre-test and post-test questionnaires to participants of the socialization and training of catfish hatcheries, the increase in knowledge of participants increased by 33.34% and the level of participant satisfaction with the implementation of activities includes adequate catfish hatchery equipment available (73.21%); explanation of presenters and technicians is very easy to understand (80.36%); fish hatchery training can be done continuously (71.43%), can increase participant income (80.36%); catfish hatchery training is very useful for participants (80.36%). In conclusion, the activities that have been carried out can improve the knowledge, skills, economic and social aspects of the community.